Circulating Salivary miRNA hsa-miR-221 as Clinically Validated Diagnostic Marker for Hand, Foot, and Mouth Disease in Pediatric Patients - Min, Nyo (ELSEVIER SCIENCE BV, 2020)
10.1016/j.ebiom.2018.05.006